Macroeconomic reforms in the economies in transition. - United Nations. Economic and Social Commission for Asia and the Pacific; United Nations (Bangkok : Economic and Social Commission for Asia and the Pacific ; New York : United Nations, 1995)
Relates to Vietnam, Laos, Cambodia, and the Central Asian republic.
"ST/ESCAP/1538."
"United Nations publication sales no. E.96.II.F.2"--T.p. verso.
Includes bibliographical references.
Keywords: Macroeconomics; Indochina -- Economic policy; Asia, Central -- Economic policy -- 1991-